Technology blueprint: mec crunchezz / Aufa Zulfaa Sazali...[et al.] - Sazali, Aufa Zulfaa; Mohamad Rizal, Intan Nursyazanie; Roslan, Nurul Husna; Hamdan, Norizzatul Syakirah; Zolkffry, Siti Zafirah (2017)
New product development (NPD) can be defined as an invention or innovation of new items of products that is beneficial holistically, which means not just focus individualistic, but also provide benefits for all peoples. The purpose of this invention or renovation is to fulfill the requirement of all the peoples and the market in order to make their task a lot easier. The purpose of written the new development products report is to ensure that the causes or the major barrier that facing by the user or producer of any product. Thererore, by doing this report, we can identify and analyses the main problem to get a rough sketch of the new product that going to be develop in future in order to help them. Later, we can identify and to plan the process to undergo the new product and decide whether it is suitable and practically for the user to handle this product. Besides that, to ensure the product, we use the SWOT analysis which is Strength, Weaknesses, Opportunities, and Threat of the demand from peoples, especially the consumers' demands. Then, we try to figure out and recommending some of our ideas verbally to most consumers and we decided on majorities decision.So, we come out with new product that emphasize for most users and not just based on certain categories of consumers. Therefore, our new product is available mostly for majorities' consumers. Last but not least, we wrap up this report with a conclusion for this new product of development.